2011
DOI: 10.5402/2011/261585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug Utilization Patterns during Initial Treatment in the Emergency Room: A Retroprospective Pharmacoepidemiological Study

Abstract: Background. We assessed the prescribing trends, average number of drugs per prescription, and cost per prescription during the initial contact of the patient with the physician in emergency room. Methods. This retro-prospective study was conducted over a period of six months. Medical records of two hundred patients were reviewed for prescribing patterns. Results. 52 different types of drugs (996 drugs) were prescribed in total 200 prescriptions during the mean time spent in emergency room of 2.8 ± 1.4 hours. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…One another study shows that average drugs prescribed was 4.2±1.2/prescription, which is in contrast to our study results. 9 This difference could be due to the fact that the patients were followed only for the duration of initial 3 h of hospital stay in the previous study (Table 5). Among the cardiovascular disorders (n=65), acute coronary syndrome was present in 15 individuals followed by congestive heart failure in 13 patients and arterial fibrillation was present in 11 patients, cardiogenic shock was present in 10 patients followed by pulmonary embolism (n=10) and hypertensive emergency in 6 patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One another study shows that average drugs prescribed was 4.2±1.2/prescription, which is in contrast to our study results. 9 This difference could be due to the fact that the patients were followed only for the duration of initial 3 h of hospital stay in the previous study (Table 5). Among the cardiovascular disorders (n=65), acute coronary syndrome was present in 15 individuals followed by congestive heart failure in 13 patients and arterial fibrillation was present in 11 patients, cardiogenic shock was present in 10 patients followed by pulmonary embolism (n=10) and hypertensive emergency in 6 patients.…”
Section: Discussionmentioning
confidence: 87%
“…About 81.14% of drugs were prescribed by brand name as compared with study of emergency room, in which 95% of drugs were prescribed by brand names. 9 By using generic names of prescription chance of duplication of drug products is eliminated and cost to the patient decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of polypharmacy was found to be 4.9 by Kaur et al, 4.2 by Cheekavolu et al whereas Barot et al has reported the use of drugs to be as high as 9.9±2.5 drugs per prescription. 2,3,9 More than fifty percent of drugs were prescribed by brand name. Physician prefers to write brand names which may be an evidence of vigorous promotional strategies by pharmaceutical companies.…”
Section: Discussionmentioning
confidence: 99%
“…Irrational prescription leads to unproductive and unsafe treatment, that manifests in either exacerbation or prolongation of illness, distress and harm to the patient or higher costs. 3 Appropriate medication use is of both clinical and economic significance to any health system and should be given adequate attention. 4 There are very few pharmaco-epidemiological studies in developing countries about prescribing patterns.…”
Section: Introductionmentioning
confidence: 99%
“…[17] A study in ED in the USA on elderly patients (n = 124) displayed to be found a normal number for each drug of 8.6 (range 021). Two investigations directed in India (n = 200 and n = 259) demonstrated an average of number drugs per prescription of 4.2 and 3.3, respectively, [18,19] in these two studies, cardiovascular system diseases and liver cirrhosis disease had the highest average number of drugs per prescription (5.4 and 3.9, individually). [20] One explanation behind the higher average number of drugs per prescription in the USA contrasted and the WHO standard is that doctors have a tendency to oversee poly-pharmacy amid the underlying contact with the patient while the conclusion is not yet affirmed and sitting tight for laboratory comes about.…”
Section: Indicator Valuementioning
confidence: 99%